Scalenectomy Anterior as an Option for Thoracal Outlet Syndrome - Bari, Yunus Abdul; Rafif Amir, Muhammad; Suroto, Heri; Pradana, Reyhan Pradnya (Journal La Medihealtico, 2024)
The term "thoracic outlet syndrome" (TOS) refers to a collection of conditions that cause compression of the neurovasculature as it leaves the thoracic outlet. The condition was initially identified in 1956. The scalene triangle, the costoclavicular space, and the subcoracoid region are the three spaces where TOS typically occurs. The brachial plexus, the axillary artery and vein, and the subclavian artery and vein are all of the structures involved with TOS. A 38-year-old male presented to the orthopaedic department. He complained about weakness and numbness in her left arm that had been present for 15 years. The complaints had been aggravated over the last 3 years which was exacerbated by activities that required her to lift her arm. The most prevalent causes of TOS are congenital, traumatic, or functional. TOS is classified into three categories based on its clinical presentation: neurogenic (nTOS), venous (vTOS), and arterial (aTOS), with nTOS being the most frequent. Treatment for Thoracal Outlet Syndrome is conservative. However, if conservative treatment does not work well, operative treatment is needed.